Factors Affecting the Growth of Micro, Small, and Medium Enterprises in the Bangka Belitung Islands Province - Kholil Harahap; Wahyu Murti; Sugianto Saleh (Jurnal Multidisiplin Indonesia, 2025)
The problem faced by developing countries is the welfare of their country. One of Indonesia's national development plans was carried out in order to realize efforts to improve community welfare. This research aims to analyze the factors that influence the growth of MSMEs in the Bangka Belitung Islands Province. The research method used in the research is ordinary least squares multiple and simple linear regression on panel data. The independent variables used are financing, investment, cooperatives, infrastructure and tourist visits, while the dependent variable is the growth of the MSME sector. The research results show that: Financing, investment, cooperatives, infrastructure and tourist visits simultaneously and partially influence the empowerment of the MSME sector.